Development of techniques for the isolation and characterisation of human monoclonal antibodies from Hepatitis C virus infected individuals - Edwards, Victoria C. (2012)
Infection with hepatitis C virus (HCV) is cleared spontaneously in only 20% of cases with the majority of individuals developing a chronic infection. This discrepancy in disease outcome is incompletely understood but current understanding of the immune response to HCV suggests that rapid induction of a broadly neutralising antibody (nAb) response leads to resolution of acute infection. The majority of nAb identified target the envelope glycoproteins, particularly E2, and most appear to inhibit binding of E2 to the cellular receptor CD81. Antibodies targeting other interactions, such as those with the receptor CLDN or the fusion determinant, are underrepresented in the repertoire of anti-HCV antibodies. However, the antibody discovery process may have been biased by the nature of the assays used. Therefore new assays are needed to enable the discovery and characterisation of antibodies in an unbiased manner. To facilitate this, a novel insect cell display library was developed for mapping antibody-binding epitopes. Cells expressing specific E2 mutants provided the necessary proof-of-principle that loss of antibody binding could be detected in this system before a library expressing randomly mutated E2 was developed. Sorting experiments demonstrated that single cells could be isolated and enriched based on loss of antibody binding. Secondly, a method for characterising the immunoglobulin (Ig) genes of HCV infected patients was developed; Ig genes were isolated from small numbers of B cells and the sequences analysed. Finally, a patient cohort was studied with a view to investigating the evolution of the antibody response during early infection. The unreliable nature of the samples prevented such analysis; however a DNA fingerprinting method of testing the origin and relatedness of serum samples was developed. This will improve the reliability of future studies. Together these methods provide a work model for the assessment of samples and the isolation and characterisation of antibodies.